Arterial Pedal Arch Revascularization Impact on the Clinical Results in Critical Lower Limb Ischemia - Igor I. Katelnitskiy (Journal of Global Pharma Technology, 2020)
Background: There are still many unresolved problems that reduce frequency of clinical and technical success of angioplasty of lower limb arteries. One of such problems is impact of the arterial pedal arch revascularization on the clinical result of angioplasty in patients with IV class critical lower limb ischemia according to Pokrovsky-Fontaine classification. Material and methods: The results of treatment of 98 patients with peripheral arterial disease (PAD), complicated by critical lower limb ischemia of IV class according to Pokrovsky-Fontaine classification were analyzed in the early postoperative period and 1 year later after the completed angioplasty. Patients were divided into two comparable groups: the first group-the patients with the arterial pedal arch revascularization, the second group – the patients whom it had been impossible to revascularize the arterial arch. Results: “Good result” in patients of the first group in the early postoperative period and one year later was 23.1% and 22.7% respectively. In the patients of the second group-9.2% and 5.6%. The both group patients avoided amputations in the early postoperative period, but one year later 53.3% of the second group patients with the “unsatisfactory result” underwent amputation. Conclusions: According to the results, the arterial pedal arch revascularization influences on the clinical results and decreases the quantity of amputations in patients with purulent-necrotic changes in the lower limb. Keywords: Critical low limb ischemia; Arterial pedal arch; Revascularization; Transluminal balloon angioplasty.